2017
DOI: 10.1103/physreve.96.012310
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical properties of the herding voter model with and without noise

Abstract: Collective leadership and herding may arise in standard models of opinion dynamics as an interplay of a strong separation of time scales within the population and its hierarchical organization. Using the voter model as a simple opinion formation model, we show that, in the herding phase, a group of agents become effectively the leaders of the dynamics while the rest of the population follow blindly their opinion. Interestingly, in some cases such herding dynamics accelerates the time to consensus, which then b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Initially termed as "inertia" [25], it was shown that the slowing down of the microscopic dynamics induced via aging actually decreased the time needed to reach the macroscopically ordered state state of consensus. In this respect, and in alignment with previous studies [25][26][27][28][29][30][31], we consider that aging acts on the mechanism associated with social contagion.…”
Section: Introductionsupporting
confidence: 64%
“…Initially termed as "inertia" [25], it was shown that the slowing down of the microscopic dynamics induced via aging actually decreased the time needed to reach the macroscopically ordered state state of consensus. In this respect, and in alignment with previous studies [25][26][27][28][29][30][31], we consider that aging acts on the mechanism associated with social contagion.…”
Section: Introductionsupporting
confidence: 64%
“…We study the effect of this type of aging in the noisy voter model, also known as the Kirman model [9]. It has appeared in several contexts, such as percolation [33], surface-catalytic reactions [34,35], probability theory [36], opinion dynamics [37][38][39][40][41], and economics [9,42,43]. The dynamics of this binary-state model is driven by two mechanisms: noise, defined as spontaneous state changes at a rate a, and a pair-wise interaction by which an element blindly copies the state of a randomly chosen neighbor.…”
Section: Introductionmentioning
confidence: 99%
“…Substituting (15) and ( 16) into (12), after taking the integral, one can obtain an exact expression for the stationary probability density ρ st (m). However, to describe the behavior of our system, it will be enough to find and study the stability of the extrema of the function ρ st (m).…”
Section: Analytical Resultsmentioning
confidence: 99%